ҚАЗАҚСТАНДА ШАҒАЛАДАН БӨЛІП АЛЫНҒАН ТИПТАРМАҒЫ Н5N1 ЖОҒАРЫПАТОГЕНДІ ТҰМАУ А ВИРУСЫНЫҢ БЕТКЕЙЛІК АҚУЫЗДАРЫ ГЕНДЕРІН ФИЛОГЕНЕТИКАЛЫҚ ТАЛДАУ - K. Kh. Zhumatov; A. I. Kydyrmanov; K. O. Karamendin; K. D. Daulbayeva; E. Ya. Khan; E. T. Kasymbekov; E. T. Kasymbekov; M. Kh. Sayatov; S. Fereidouni (Scientific Journal of Pedagogy and Economics, 2018)
The article presents the results of phylogenetic analysis of surface protein hemagglutinin and neuraminidase genes of influenza A virus of H5N1 subtype isolated from gull in the territory of the Republic of Kazakhstan in 2015. Cluster affiliation of Kazakhstan isolate and relationship with other influenza viruses of A/H5 subtype from international database GenBank are presented. It is concluded that it is necessary to continuously monitor the avifauna of Kazakhstan in order to isolate current variants of pathogens.